Product Innovation Of Islamic Financial Institutions In The Perspective Of Sharia Economic Law - Taupik, Opik; Herdiana, Nana; Prasetyo, Yoyok (Zona Law And Public Administration Indonesia, 2024)
Product innovation in Islamic financial institutions has become a necessity in facing the ever-growing global market dynamics. This article explores the views of sharia economic law on product innovation with the aim of revealing the key role of sharia economic law in designing, implementing and regulating innovative sharia financial products. The basic concepts of sharia economic law, such as the prohibition of usury, the prohibition of maysir and gharar, as well as the principle of zakat, play a central role in forming the framework for sharia product innovation. However, Islamic financial institution product innovation is also faced with a number of challenges and controversies, such as legal considerations, supervision and ethical issues. This article considers these challenges and proposes possible solutions to overcome them. By combining a sharia economic law perspective with sharia financial product innovation, this article provides in-depth insight into how these products can develop in accordance with sharia principles, as well as their impact on sharia economic development more broadly.